Analisis Kinerja Personel Air Traffic Control pada Approach Control Unit di Airnav Indonesia Cabang Pontianak - Neloe, Rainaldo; Sugih Arti, Endang; Zeda, Fardan (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
This research was conducted at Perum LPPNPI Pontianak Branch Office. The variable studied was a single variable, namely the performance of ATC personnel. The method used in this research is descriptive method with a mixed approach. The data technique used a questionnaire that was distributed to the sample and then carried out the data processing requirements in the form of validity, reliability and gap analysis tests. Analysis of research results is still protected for ATC personnel in providing flight traffic services. To overcome this problem, it is necessary to improve facilities and infrastructure as well as the division of Job Position in only 1 sector in order to improve the performance of ATC personnel in providing flight traffic services.